MENINGKATKAN KETERAMPILAN KINESTETIK MELALUI PERMAINAN OUTBOUND PADA ANAK USIA DINI 5-6 TAHUN DI TAMAN KANAK-KANAK BUNDA KECAMATAN BIRINGKANAYA KOTA MAKASSAR - Nashirah, Ulfa Nur Nashirah; Nurhidaya S, A.Rezky Nurhidaya S (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2023)
Ulfa Nur Nasrhirah, et al, Improving Children's Gross Motor Skills through Outbound Games for Children Aged 5-6 Years at Mother's Kindergarten. Children's gross motor skills are skills that involve large muscles in various parts of the body. One of the learning methods that can develop gross motor skills is a boardwalk. The aim of the researchers was to find out how to develop gross motor skills through outbound activities in children aged 5-6 years at Bunda Kindergarten. This type of research is classroom action research. The research data from Cycle I obtained a percentage of 64.2% and Cycle II obtained an increase in the percentage of 82%. Improving gross motor skills through outbound activities can be seen by children playing happily, children are motivated to win and children still hope that the game will be repeated/continued.